2014
DOI: 10.1088/1741-2560/11/1/016006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the effects of the human dura on macro- and micro-electrocorticographic recordings

Abstract: Objective Electrocorticography (ECoG) electrodes implanted on the surface of the brain have recently emerged as a potential signal platform for brain-computer interface (BCI) systems. While clinical ECoG electrodes are currently implanted beneath the dura, epidural electrodes could reduce the invasiveness and the potential impact of a surgical site infection. Subdural electrodes, on the other hand, while slightly more invasive, may have better signals for BCI application. Because of this balance between risk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 46 publications
3
49
1
Order By: Relevance
“…Here, we decoded continuous whole hand grasping movements and linked to motor control literature (Santello et al 1998, Ingram et al 2008) showing that the many degrees of freedom inherent to finger movements can be represented by a few principal component representations. These results can also be seen as validating prior modeling studies, which have not necessarily predicted a worsening of decoding accuracy due to the dura’s presence (Slutzky et al 2010, Bundy et al 2014), even despite lower amplitude signals (Ramon et al 2014). …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Here, we decoded continuous whole hand grasping movements and linked to motor control literature (Santello et al 1998, Ingram et al 2008) showing that the many degrees of freedom inherent to finger movements can be represented by a few principal component representations. These results can also be seen as validating prior modeling studies, which have not necessarily predicted a worsening of decoding accuracy due to the dura’s presence (Slutzky et al 2010, Bundy et al 2014), even despite lower amplitude signals (Ramon et al 2014). …”
Section: Discussionsupporting
confidence: 86%
“…Previous studies that examined the effect of the dura and CSF on neural signals concentrated primarily on the relative power spectra or amplitude of the signals (Slutzky et al 2010, Bundy et al 2014, Olson et al 2015). Here, we evaluated how useful these signals would be for BMIs by using them to decode hand movements.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, probably because of the large number of neurons contributing to the EFP/ECoG signal (Miller et al, 2009), the additional attenuation of the signal by the dura makes epidural recordings a still rare case, despite its obvious clinical advantages. A recent study in monkey somatosensory cortex indeed indicated weaker decoding performance for epidural as compared to subdural signals (Bundy et al, 2014;Farrokhi and Erfanian, 2018). On the other hand, a rodent study on forelimb movements concluded that EFPs allow for the same decoding performance than intracortical LFPs (Slutzky et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Penetration of the dura increases the risk of bacterial infection [3842]. Epidural electrodes (i.e., electrodes placed on top of the dura) provide signals of approximately comparable fidelity [43, 44]. A single electrode placed epidurally could reduce risk, which should make this approach more clinically practical.…”
Section: Discussionmentioning
confidence: 99%